Determining of tourist’s spatial behaviour and tourist movement pattern in Muar royal town, Johor - M Noor Azman, Nor Afifin Nadia; Md Sawari, Siti Salwa (2019)
Travelling acquire movement. The movement pattern was formed to deliver a meaningful purpose to travel that closely related with personal behavior characteristic. However, tourists nowadays faces limitation in their movement of journey while visiting plenty of attractions. The movement limitations can be occurred due to unsystematic transportation system and accessibility, less of tourism packages supply, and disorganized digital marketing strategy by tourism destination management. Hence, this study aims to explore the characteristic of tourist’s spatial behaviour and tourist movement pattern in urban heritage area at Muar. The research design applied in this study is qualitative method which involved grounded theory approach. Therefore, the construction of theories through gathering and analysis of data by using inductive reasoning from fieldwork observation and interviewing method. The result of this study demonstrates that the tourist spatial behaviour has influenced the tourist movement pattern in aspect socio-cultural background characteristic on visitors travel life style that consist of accommodation location, travelling purpose, mode of transportation used and special interest. In short, it will be significantly useful to know sociocultural visitor behaviour towards tourist movement pattern in Muar Royal Town Johor.